Diplomatic Marriages Between the Danube Bulgarian State and the Byzantine State - Tolan, Öner (Fırat University, 2023)
The neighborhood of the Bulgarians with Byzantium started with the settlement of some Bulgarians in the Lower Danube region under the leadership of Asparuh at the end of the 7th century. The relationship between the two states, which became neighbors in this way, will continue until the beginning of the 11th century when the Danube Bulgarian State was definitely destroyed. In this process of Danube Bulgarian political life which lasted for more than three centuries, a political relationship was maintained in which the Danube Bulgarian State had intense contacts with the Byzantine State. In some periods, Bulgarians and in other periods Byzantium became politically powerful and superior. Of course, as the political power has changed, the nature of the relations has also changed. Political agreements, alliances, and pledge practices are among the diplomatic methods used from time to time within the framework of this relationship. One of these diplomatic practices is diplomatic marriages. In the diplomatic relations between the two states, diplomatic marriages have been one of the important methods used and it is an important element to be taken into account when examining the Bulgarian-Byzantine relations. The aim of this study is to determine the marriage ties planned to be established between the members of the dynasty within the framework of the political relations of the Danube Bulgarian State and the Byzantine State and to reveal on which political ground they developed.

Bulgarların Bizans ile olan komşuluğu, Kubrat Han’ın başında bulunduğu Karadeniz’in kuzeyindeki siyasi yapının dağılmasının ardından VII. yüzyıl sonlarında bir kısım Bulgarların Asparuh liderliğinde Aşağı Tuna bölgesine gelip yerleşmesi ile başladı. Bu şekilde sınır komşusu haline gelen iki devletin birbiri ile olan ilişkisi, Tuna Bulgar Devleti’nin kesin olarak yıkıldığı XI. yüzyılın başlarına kadar devam edecektir. Bu süreç içerisinde Tuna Bulgar Devleti’nin üç asırdan uzun sürmüş olan siyasi hayatı boyunca komşuluk yaptığı Bizans Devleti ile dostluk ve düşmanlık çizgisinde gidip gelen yoğun temasların yaşandığı bir siyasi ilişki sürdürülmüştür. Bazı dönemlerde Bulgarlar, bazı dönemlerde de Bizans siyasi olarak güçlü ve üstün konuma gelmiştir. Elbette siyasi güç değiştiği ölçüde ilişkilerin niteliği de değişmiştir. Siyasi anlaşmalar, ittifaklar, rehin uygulamaları bu ilişki çerçevesinde zaman zaman başvurulan diplomatik yöntemler arasındadır. İşte bu diplomatik uygulamalardan biri de siyasi evliliklerdir. İki devlet arasındaki diplomatik ilişkilerde, siyasi evlilikler, başvurulan önemli yöntemlerden biri olmuştur ve Bulgar-Bizans ilişkileri incelenirken dikkate alınması gereken önemli bir unsurdur. Bu çalışmanın amacı Tuna Bulgar Devleti ile Bizans Devletinin siyasi ilişkileri çerçevesinde hanedana mensup kişiler arasında kurulması planlanan evlilik bağlarını tespit etmek ve bunların hangi politik zeminde geliştiğini ortaya koymaktır.
TUNA BULGAR DEVLETİ İLE BİZANS DEVLETİ ARASINDA SİYASÎ EVLİLİKLER
Keywords: Cultural Studies (Other); Kültürel çalışmalar (Diğer)